Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata) - Conradie, Werner; Branch, William R.; Watson, Gillian (Zootaxa, 2019)
The Port Elizabeth Museum herpetology collection contains 407 type specimens, representing 70 primary and 55 secondary squamate types. The type series comprise 93 African taxa (84 lizards and 9 snakes), of which 75 are still regarded as valid. It is the third largest primary reptile type collection in Africa. This is the first catalogue of this important African squamate type collection. It provides the original name, original publication date, journal volume number and pagination, reference to illustrations, current name, museum collection number, type locality, and notes on the status of all types and important additional non-type material mentioned in historical descriptions. Photographs of all primary types, as well as original illustrated material are provided.